2018
DOI: 10.14814/phy2.13601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speed endurance training and reduced training volume on running economy and single muscle fiber adaptations in trained runners

Abstract: The aim of the present study was to examine whether improved running economy with a period of speed endurance training and reduced training volume could be related to adaptations in specific muscle fibers. Twenty trained male (n = 14) and female (n = 6) runners (maximum oxygen consumption (VO2‐max): 56.4 ± 4.6 mL/min/kg) completed a 40‐day intervention with 10 sessions of speed endurance training (5–10 × 30‐sec maximal running) and a reduced (36%) volume of training. Before and after the intervention, a muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
2
20
3
Order By: Relevance
“…Particularly, in that previous study, the stimulated muscles showed a non-pathological adaptive decrease in volume coinciding with a transformation of the muscle fiber-type towards phenotypes which are less susceptible to fatigue (i.e., fiber types 2a and 1) but tend to present smaller cross-sectional areas and thus occupy a smaller muscle volume 27 . It is worth noting that similar muscle changes have been reported in studies of high endurance training both in rats and humans 3032 . On this basis, the strong negative correlation reported here is important for understanding the mechanisms guiding entheseal variation in response to activity.…”
Section: Discussionsupporting
confidence: 75%
“…Particularly, in that previous study, the stimulated muscles showed a non-pathological adaptive decrease in volume coinciding with a transformation of the muscle fiber-type towards phenotypes which are less susceptible to fatigue (i.e., fiber types 2a and 1) but tend to present smaller cross-sectional areas and thus occupy a smaller muscle volume 27 . It is worth noting that similar muscle changes have been reported in studies of high endurance training both in rats and humans 3032 . On this basis, the strong negative correlation reported here is important for understanding the mechanisms guiding entheseal variation in response to activity.…”
Section: Discussionsupporting
confidence: 75%
“…; Skovgaard et al. ) and may be related to larger abundance in type I than type II muscle fibers (Howald et al. ; Thomassen et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Skovgaard et al. ). Thus, the aim of this study was to compare the effect of MICT without or with inclusion of repeated 30‐s sprints on adaptations in mitochondrial proteins in type I and II muscle fibers, as well as on cycling performance.…”
Section: Introductionmentioning
confidence: 97%
“…Short maximal-effort intervals have been reported to be of less strain compared to longer HIT-intervals (Valstad et al, 2018) and might serve as an intensive stimulus, sufficient for maintaining endurance performance in shorter periods of reduced training volume. For example, the addition of sprint training in periods with 25-65% reductions in training volume has shown to maintain endurance performance-determining factors in moderately trained athletes (VO 2max , muscle oxidative capacity, and capillarization; Joyner and Coyle, 2008) and improved performance at or above intensities eliciting VO 2max (Bangsbo et al, 2009;Iaia et al, 2009;Skovgaard et al, 2018). Furthermore, including 30-s sprints every 10 min in 60-min LIT-sessions during an 8-week intervention has recently shown improved performance in trained cyclists (Gunnarsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%